IC 9392 Mechanical Excavation Systems (In Three Parts) 1. Drill-Split Narrow-Vein And Longwall Mining (The National Institute for Occupational Safety and Health (NIOSH), 1994)
In this U.S. Bureau of Mines report, two drill-split mechanical excavation mining system concepts are described, casted, and cost compared with conventional drill-blast mining systems. The concepts for the two drill-split mechanical excavation mining systems presented are (1) a method for steeply dipping narrow veins 0.6 to 1.2 m wide and (2) a longwall method for fiat-lying tabular ores. In the proposed systems, 70 to 80 pet of the ore is disposed of underground as backfill. For sortable ores, face area crushing, sorting, and direct stowage of run-of-mine waste and low-grade ores are proposed. The underground sorting and stowing of waste reduce materials handling, processing, and waste disposal costs by reducing the quality of ore transported to the surface by 70 to 80 pet (by volume). Because many of the tools and techniques proposed for use in these systems have little or no historical mining industry use, cost assignations are heavily influenced by engineering judgments and presented as prefeasibility-level cost estimates. These estimates, presented as discounted-cash-flow-rate-of-return (DCFROR) values, show the proposed systems to be at least as profitable as, and in some cases 50 pet more profitable than, conventional drill-blast mining.